The impact of the COVID-19 lockdown on orthopaedic emergency presentations in a remote and rural population - Ahmed S. Elhalawany; James Beastall; Gerard Cousins (Bone & Joint Open, 2020)
Aims: COVID-19 remains the major focus of healthcare provision. Managing orthopaedic emergencies effectively, while at the same time protecting patients and staff, remains a challenge. We explore how the UK lockdown affected the rate, distribution, and type of orthopaedic emergency department (ED) presentations, using the same period in 2019 as reference. This article discusses considerations for the ED and trauma wards to help to maintain the safety of patients and healthcare providers with an emphasis on more remote geography. Methods: The study was conducted from 23 March 2020 to 5 May 2020 during the full lockdown period (2020 group) and compared to the same time frame in 2019 (2019 group). Included are all patients who attended the ED at Raigmore Hospital during this period from both the local area and tertiary referral from throughout the UK Highlands. Data was collected and analyzed through the ED Information System (EDIS) as well as ward and theatre records. Results: A total of 1,978 patients presented to the ED during the lockdown period, compared to 4,777 patients in the same timeframe in 2019; a reduction of 58.6%. Orthopaedic presentations in 2020 and 2019 were 736 (37.2%) and 1,729 (36.2%) respectively, representing a 57.4% reduction. During the lockdown, 43.6% of operations were major procedures (n = 48) and 56.4% were minor procedures (n = 62), representing a significant proportional shift. Conclusion: During the COVID- 19 lockdown period there was a significant reduction in ED attendances and orthopaedic presentations compared to 2019. We also observed that there was a proportional increase in fractures in elderly patients and in minor injuries requiring surgery. These represented the majority of the orthopaedic workload during the lockdown period of 2020. Given this shift towards smaller surgical procedures, we suggest that access to a minor operating theatre in or close to ED would be desirable in the event of a second wave or future crisis.